ANALISA KEPUASAN MASYARAKAT TENTANG PELAYANAN PUBLIK (Studi kasus IGD RSUD Bangkinang Kabupaten Kampar) - RIMA, FAJRUL LEPI; YULIANI, FEBRI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Emergency Room is one of public organization oriented to service that aims toserve and provide satisfaction to the people, especially on the health aspects. To givesatisfaction to the patient the nurse must provide nursing care in accordance with theexpected expertise and skills possessed by nurse, especially nurse on duty in the ER.Emergency Room care is a service for people who need fast and professionalhandling. Improved service must be made priority Hospitals, especially in theemergency room of the installation in order to create expectations and patientssatisfaction.The are some barriers or obstacles in providing health care to patientsEmergency Room, among others, the low Human Resources owned by the EmergecyRoom in providing health services, lack of health care facilities supporting works,and hospitality workers and the lack labor discipline medical residing in theEmergency Room Bangkinang hospitals in providing health services. In order toovercome barriers or obstacles in providing health care in the Emergency Room then,required quality of health services, which on one hand can satisfy the users of theservices, and on the other hand its implementation procedures in accordance with thecode of ethics and standards that have been set.The concept of the theory is a theory that researchers use health servicesconsisting of available, sustainable, Acceptable and reasonable, easy to archieve, easyto reach and grade. This study used qualitative research methods to the assessment ofdescriptive data. In collecting the data, the researchers used interview thecniques,observation and study literature. By using key informant and the informant as asupplementary source of information.The results of this study indicate that, Customer Satisfaction Analysis OnPublic Service. ( Study case in Bangkinang Hospital Emergency Room ) assessed tobe less, due to the lack of human resources and facilities owned by the HospitalEmergency Room Bangkinang and there are many grievances felt by the customer’sHospital for the lack of service provided by the Emergency Room.Keywords : Satisfaction, Service, Installation Emergency